Continuation and effectiveness of programme and non-programme methods of family planning in Sri Lanka - Shyam Thapa; David Hamill; Philip Lampe (Asia-Pacific Population Journal, 1993)
The clinical efficacy of various contraceptive methods is well known. However, relatively little is known about their use-effectiveness (which refers to both technical failure of a method and the failure to use a method properly in actual life conditions, especially in developing countries). Use-effectiveness data for programme as well as non-programme methods are necessary for assessing the impact of contraceptive use on fertility (Bongaarts and Potter, 1983).